If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2n + -2 + 2n + -4 = 5 Reorder the terms: -2 + -4 + 2n + 2n = 5 Combine like terms: -2 + -4 = -6 -6 + 2n + 2n = 5 Combine like terms: 2n + 2n = 4n -6 + 4n = 5 Solving -6 + 4n = 5 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 4n = 5 + 6 Combine like terms: -6 + 6 = 0 0 + 4n = 5 + 6 4n = 5 + 6 Combine like terms: 5 + 6 = 11 4n = 11 Divide each side by '4'. n = 2.75 Simplifying n = 2.75
| 5v+23=-2 | | 4x-8=2ax-2b | | 7/3(-16)-12= | | 5.5(-3*7.5)= | | x-0.13x= | | 3(7)+7y=84 | | -8(x+9)+8=-64 | | Y+8+y=5+2(y-6) | | 14x^3+35x-7x=0 | | 2u+8=-18 | | 2/3(-16)+4= | | 8x+11=14x-1 | | -15-2y=18 | | -12=2+2v+5v | | 9t+11=11 | | -40=8+-6s | | 3x+7(0)=84 | | 2(2x-5)=3(x-5)+4(2x-3) | | -24-2y=18 | | 3(0)+7y=84 | | 3(-13+1)=2(-13-5) | | 3.9=n+8.3-2.9 | | 5y+o=51 | | 4d-6=9d+2 | | x^2+x+-20=0 | | 2s+18=0 | | 8x+24x^3= | | -4.3x+3.2x=-3.52 | | 15-4n+3=2(3n-8)-9n | | -7(n-4)+7n=-7(n+4) | | 6*(13+9)-14= | | (7x-1)(3x+8)=0 |